Perlindungan Hukum Keluarga Transnasional Dalam Perspektif Hukum Keluarga Islam Dan Prinsip Non-Diskriminasi - Muhammadun; Nailah Nurkhafifah; Nur Halimatus Sa'diyyah; Achmad Zaenal Arifin (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2026)
The phenomenon of global migration has given rise to transnational families that face complex legal challenges, particularly concerning the recognition of marital status, child custody, and access to legal protection across jurisdictions. The lack of harmonization among national legal systems often leads to legal uncertainty and discriminatory practices against migrant families. This study aims to analyze legal protection for transnational families by integrating the perspective of Islamic family law and the principle of non-discrimination in international law. This research employs a qualitative approach through a systematic literature review of primary and secondary legal sources, analyzed using thematic analysis techniques. The findings indicate that although international legal instruments have affirmed the principle of non-discrimination, its implementation at the national level remains fragmented and inconsistent. From the perspective of Islamic family law, the protection of transnational families aligns with the principles of maqāṣid al-sharī‘ah, particularly the protection of lineage (ḥifẓ al-nasl) and property (ḥifẓ al-māl), which emphasize justice and protection for all family members without discrimination. Therefore, harmonization between national law, international law, and Islamic legal values is necessary to establish a fair, inclusive, and responsive legal protection system for transnational families in the context of global migration.